Características do carderno do aluno: geografia integrante do projeto São Paulo faz escola - Barbosa, Gabriela Suzart [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the year of 2008, the São Paulo State Education Department, beneath José Serra government, initialized a new renovation process in the programs and curriculum of the elementary school official net. This procedure resulted in the Sao Paulo does School Project, which evolves the curriculum proposals systematization for all subject of the School curriculum. The Department produced didactic supporting material to install the new project, this material is called Teacher Notebook, Student Notebook and Manager, which have theoretical-methodological orientation and activities to be developed in class. These materials are distributed bimonthly in all State public schools. Among documental and bibliographic research it was possible to have contact with the referred material, which brought reflection about its meaning in the geography area. It had been auxiliary for the research, the experience obtained in the Supervisioned Internship of the UNESP Ourinhos Campus Geography course and the participation as colleger in the Teaching Iniciation Scholarship Program (PIBID), in which was possible to observe closer the relation of the Student Notebook with the school, teacher and mainly the students. We realized that the Student Notebook generates many questionings. For the material analysis was necessary a reflection in a wider sphere, which includes discussions about transformations occurred in the Brazilian elementary education. The aim of this research was to comprehend aspects related to teaching containing in the Student Notebook. For the comprehension of the Sao Paulo State actual proposal meaning was needed contextualize historically the Sao Paulo does School Project and inside it the geography teaching, for that we search a preliminary study of the Paulista curriculum containing...

No ano de 2008, a Secretária de Educação do Estado de São Paulo, sob o governo de José Serra, deu início a um novo processo de renovação nos currículos e programas da rede oficial de ensino básico. Esse procedimento resultou no que se denomina Projeto São Paulo faz escola, que envolve a sistematização de propostas curriculares para todas as disciplinas do currículo escolar. Para a implantação do novo projeto, a secretaria produziu materiais de apoio didático - denominados Caderno do professor, Caderno do aluno e do Gestor, que possuem orientações teórico-metodológicas e atividades para serem desenvolvidas nas escolas. Tais materiais são distribuídos bimestralmente em todas as escolas públicas do estado. A partir de pesquisa bibliográfica e documental deu-se o contato com o referido material, o que despertou reflexões sobre o significado dele na área de Geografia. Foi auxiliar na pesquisa a experiência obtida no Estágio Supervisionado do curso de Geografia da UNESP campus de Ourinhos e a participação como bolsista do Programa de Bolsa de Iniciação à Docência (PIBID), em que pode-se observar mais de perto a relação do Caderno do aluno com a escola, professores e principalmente os alunos. Percebemos que o Caderno do aluno, gera uma série de questionamentos. Para uma análise do material em questão foi necessária uma reflexão de um contexto mais amplo, que envolve discussões a respeito das transformações ocorridas na própria educação escolar brasileira. O objetivo desta pesquisa foi compreender aspectos relacionados aos conteúdos de ensino contidos no Caderno do aluno. Para a compreensão do significado da atual proposta do Estado de São Paulo, foi preciso contextualizar historicamente o Projeto São Paulo faz escola e dentro dele o ensino de Geografia, para isso buscamos um estudo preliminar do conteúdo do currículo paulista...
Keywords: Geografia - Estudo e ensino; Geografia - Currículos; Educação e Estado